Baz Mart's Management Model in Improving the Living Standards of the Poor - Muhammad Erwin Soaduan Pohan; Mustafa Kamal Rokan; Yenni Samri Juliati Nasution (Lembaga Publikasi Ilmiah Nusantara, 2026)
The BAZ Mart program is a management model designed to improve the lives of people experiencing poverty who cannot manage or develop businesses due to physical disabilities, limited knowledge, or lack of experience. This model enables zakat funds to continue growing and expanding, ensuring their sustainability in meeting the basic needs of beneficiaries. This study aims to determine the improvement in the lives of low-income communities in Pelalawan Regency, Riau, through Baz Mart, a self-service business managed with zakat funds. Buyers are encouraged to shop at Baz Mart through collaboration among the Pelalawan Regency Government, PT Riau Andalan Pulp and Paper (RAPP), and Baznas Pelalawan's outreach program to zakat donors and the wider community under the slogan,